2006
DOI: 10.1111/j.1532-5415.2006.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Replicating the Hospital Elder Life Program in a Community Hospital and Demonstrating Effectiveness Using Quality Improvement Methodology

Abstract: HELP can be successfully replicated in a community hospital, yielding clinical and financial benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 13 publications
1
101
0
8
Order By: Relevance
“…Another key strength of the study is that all study patients received non-pharmacologic interventions to reduce the risk of delirium, including frequent reorientation, cognitive stimulation, early mobilization, sleep hygiene, and use of hearing or vision aids. Thus, while their baseline rate of delirium in the placebo group (23%) may seem low when compared to other trials of delirium interventions, this rate is consistent with other studies that utilized non-pharmacologic interventions (15). The study was limited by enrollment of patients after surgery, many of whom required consent via proxy due to medication administration and/or altered mentation.…”
Section: Commentarymentioning
confidence: 62%
See 1 more Smart Citation
“…Another key strength of the study is that all study patients received non-pharmacologic interventions to reduce the risk of delirium, including frequent reorientation, cognitive stimulation, early mobilization, sleep hygiene, and use of hearing or vision aids. Thus, while their baseline rate of delirium in the placebo group (23%) may seem low when compared to other trials of delirium interventions, this rate is consistent with other studies that utilized non-pharmacologic interventions (15). The study was limited by enrollment of patients after surgery, many of whom required consent via proxy due to medication administration and/or altered mentation.…”
Section: Commentarymentioning
confidence: 62%
“…The impact that delirium has on healthcare costs and patient outcomes has led to a number of interventions to prevent it or reduce its duration, but unfortunately the high prevalence of delirium persists despite these attempts. Many studies of therapies to prevent postoperative or ICU delirium have focused on nonpharmacologic interventions, including multicomponent care pathways, geriatrics consultation, optimization of the patient's environment, enforcing appropriate sleep hygiene, and utilization of sensory aids (14)(15)(16)(17)(18)(19). Even with multiple non-pharmacologic measures, however, delirium persists in the studied populations.…”
mentioning
confidence: 99%
“…Protocols, trained staff, and physical modifications targeted at the geriatric patient in inpatient settings have already been shown to successfully reduce the risk of delirium, iatrogenic complications, cost, hospital length of stay, and transfer to long-term care facilities, while increasing patient and provider satisfaction and preserving patient function. [14][15][16][17] It has recently been shown that these programs are replicable in community hospitals, demonstrating the widespread applicability and effectiveness of geriatricfocused interventions for inpatient geriatric care. The proposed GEDIs would initially be targeted toward patients aged 65 and older and could potentially be implemented (incrementally, depending on fiscal, physical, and demographic constraints of hospital systems) in all types of EDs.…”
Section: Geriatric Emergency Department Interventionsmentioning
confidence: 99%
“…21 The initiation of regularly scheduled psychoactive medications while hospitalized should be discouraged. 4 Finally, nonpharmacologic interventions have demonstrated efficacy in preventing delirium in the elderly individuals while hospitalized (Table 3), 11,23 and the neurologist evaluating a patient preoperatively should comment on these when appropriate. In a group of elderly patients treated with these and other interventions when appropriate, only 10% developed delirium compared to 15% in a nonintervention control group 11 ; while in a community hospital setting similar interventions led to a 35% relative reduction in delirium.…”
Section: Disturbances Of Consciousness: Delirium and Dementiamentioning
confidence: 99%